Analisis Peran Survei Lapangan dalam Verifikasi Mustahik sebagai Instrumen Akuntabilitas Pengelolaan Zakat pada BAZNAS Kabupaten Tegal - Fajar Muttaqin; Nurul Wulandari Putri (Epsilon Journal of Management, 2026)
. This study aims to analyze the role of field surveys in the verification process of mustahik as an effort to enhance accountability in zakat management at BAZNAS Kabupaten Tegal. Zakat management in modern institutions requires accurate targeting to ensure that distribution aligns with Islamic principles and effectively addresses social welfare issues. This research employs a descriptive qualitative approach, utilizing observation, in-depth interviews, documentation, and literature study as data collection techniques. The findings reveal that field surveys serve as a primary instrument in validating administrative data by directly observing the socio-economic conditions of prospective beneficiaries. This process enables more accurate and objective decision-making in determining mustahik eligibility. Furthermore, field surveys contribute significantly to improving transparency, accountability, and the precision of zakat distribution. However, the implementation of field surveys faces several challenges, including limited human resources, time constraints, and the potential for subjective assessment. Despite these limitations, field surveys remain a crucial operational mechanism in ensuring accountable zakat management. This study highlights the importance of strengthening survey implementation through capacity building and the integration of information technology to improve efficiency and data accuracy.